Subjective Mental Health, Peer Relations, Family, and School Environment in Adolescents with Intellectual Developmental Disorder: A First Report of a New Questionnaire Administered on Tablet PCs. Issue 4 (1st October 2016) - Boström, Petra; Johnels, Jakob Åsberg; Thorson, Maria; Broberg, Malin
ABSTRACT: Few studies have explored the subjective mental health of adolescents with intellectual disabilities, while proxy ratings indicate an overrepresentation of mental health problems. The present study reports on the design and an initial empirical evaluation of the Well-being in Special Education Questionnaire (WellSEQ). Questions, response scales, and an application for tablet PCs were developed in cooperation with students and teachers in special education schools. One hundred and thirteen students (age 12–16) and their parents and teachers participated. Positive results in terms of test-retest reliability, internal consistency of scales, and response rates were obtained. Level of reading appeared to affect the students' understanding of items. Teachers' and parents' ratings on the WellSEQ correlated well with established measures. Correlations between proxy ratings and students' reports varied. The questionnaire and technology of WellSEQ may enable students with IDD to participate independently in research with good completion rates and reliable responding.